2012
DOI: 10.1038/aja.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icarisid II on diabetic rats with erectile dysfunction and its potential mechanism via assessment of AGEs, autophagy, mTOR and the NO–cGMP pathway

Abstract: Erectile dysfunction (ED) is a major complication of diabetes mellitus. Icariin has been shown to enhance erectile function through its bioactive form, icarisid II. This study investigates the effects of icarisid II on diabetic rats with ED and its potential mechanism via the assessment of advanced glycosylation end products (AGEs), autophagy, mTOR and the NO-cGMP pathway. Icarisid II was extracted from icariin by an enzymatic method. In the control and diabetic ED groups, rats were administered normal saline;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 44 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…The present study showed that induction of diabetes with STZ resulted in a decline in erectile function, as indicated by a decrease in both endothelium‐dependent and neurogenic corpus cavernosum relaxation of diabetic rats. This result confirmed previous findings indicating that diabetes was able to induce ED in experimental and clinical studies . The diminished ACh‐induced endothelium‐dependent relaxation can be explained by several mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that induction of diabetes with STZ resulted in a decline in erectile function, as indicated by a decrease in both endothelium‐dependent and neurogenic corpus cavernosum relaxation of diabetic rats. This result confirmed previous findings indicating that diabetes was able to induce ED in experimental and clinical studies . The diminished ACh‐induced endothelium‐dependent relaxation can be explained by several mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…With antioxidants being so abundant in many plants, they could have an important influence on human health. Flavonoids are known to improve erectile function by their antioxidant and anti‐inflammatory properties (Yang, Gao, Wang, Su, & Xing, ; Zhang et al., ). In present study, treatment with RT to diabetic rats improved the cGMP levels in penile tissue as compared to untreated diabetic rats, and this may be justified by its pharmacological potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Due to aphrodisiac properties induction in Chinese goat, E. grandiflorum is commonly known as horny goat weed. Icariin, a flavonol glycoside as active ingredient of this plant induce the nitric oxide (NO) synthesis in penis, 2 cavernosal smooth muscle where NO acts as inhibitor of cGMP-specific phosphodiesterase type 5 (PDE5), 3 and boost the proliferation of smooth muscle, and reduce the formation of advanced glycation end product 4 and caricaturist endogenous androgens. 5 These beneficial effects of Epimedium species are due to the presence of various phytochemical constituents; and about over 260 including alkaloids, flavonoids, proteins, glycosides, bioactive peptides, waxes, amino acids, phyto-hormones are responsible for beneficiary activities, have been isolated.…”
Section: Introductionmentioning
confidence: 99%